Nivel de actividad física en el adulto mayor en Microred José Leonardo Ortiz, 2019 - Peralta Guerrero, Liseth Anali (2020)
Objective: To determine the level of physical activity in older adults who attend the older adult program in the health facilities of the Microred José Leonardo Ortiz, 2019. Method: A quantitative, descriptive, cross-sectional study, 178 older adults participated; Distributed by stratified sampling in the six Microred health facilities, the participants were chosen by convenience sampling. The questionnaire was applied, subjected to a pilot test with acceptable reliability of 0.692 according to Cronbach's Alpha. This questionnaire evaluates physical activity: domestic, transportation and free time. Main results: Indicate that: 56.7% performed a high level of physical activity; With respect to domestic activities, more than 50% reported doing light, heavy work and preparing their food; with relation to the displacement, 61.2% use public transport and 60.7% walk; and 50.6% carry out leisure activities; and the least performed physical activities were, not participating in walks and not riding a bicycle. Conclusion: Older adults carry out a high level of physical activity, and are always doing domestic activities, use public transport and do recreational activities in their free time. It is a priority to have specialized professionals for the comprehensive care of the elderly and to work at a multisectoral and family level to promote physical activity programs at this age.